Pengaruh Gaya Kepemimpinan, Kepuasan Kerja dan Kompensasi Terhadap Kinerja Pegawai PT PLN (Persero) Wilayah Sulselrabar - Hamzih, Muhammad; Amrah, Wahida (Journal of Management Sains (JMS), 2023)
This study aims to: (1) the effect of leadership style on employee performance; (2) To determine the effect of job satisfaction on employee performance; (3) To determine the effect of compensation to employee performance; (4) To determine jointly the influence of leadership style, job satisfaction and compensation to employee performance. Type of this research is quantitative data. The object of this research is PT. PLN (Persero) Region Sulselrabar. The sampling technique using census method that all employees of PT. PLN PLN (Persero) Region Sulselrabar. Methods of data collection is done by distributing questionnaires. The results showed that (1) style of leadership and significant positive effect on employee performance; (2) job satisfaction and significant positive effect on employee performance; (3) compensation positive and significant effect on employee performance; (4) leadership style, job satisfaction and compensation together positive and significant impact on employee performance.